Territorialização do capital extrativista mineral sobre áreas de Reforma Agrária: da voracidade do capital à luta pela defesa da terra e da vida no Assentamento Mucatu/PB - Lourenço, Nielson Polucena (2021)
We are currently undergoing a dramatic expansion of extractivist mineral capital in Latin America. This movement has been spoliating native, quilombola, and settled peasant communities, thus redefining and undoing forms of local political, economic and cultural organizations, besides causing irreversible social and environmental impacts. In this context, mining companies have been expanding their interest in rural settlements areas. Particularly, in the province of Paraíba, 109 settlements that altogether encompass 129,506 hectares and 6,433 families are presented under the watchful eye of mining companies. The main objective of this thesis concerns the analysis of the territorial disputes in the countryside that emerged from the territorialisation of extractivist mineral capital located in rural settlement areas. The main focus of our analysis was the expansion of the cement industry in Paraíba’s south coast and strategies of resistance of the local peasantry force. Regarding the research subject, we addressed the conflict amidst the peasants of the Mucatu settlement (particularly one of its communities, João Gomes), which is centrally located between Alhandra-PB and Pitimbu-PB counties, and the Elizabeth Cimentos cement company. The conflict started in 2011 when Elizabeth Cimentos acquired 206,700 hectares within the settlement area to assemble its productive industrial unit. This event was sufficient to cause radical changes in the lifestyle of local communities. To properly approach our research subject, we used different methods and sources of information such as a) bibliographical research, b) desk research, c) secondary data surveys, d) newspapers reports, and e) field research. We also presented a discussion of several points to properly comprehend the spatial aspect of the conflict, namely the production of space from the perspective of capital accumulation, the territory as a fraction of a space mediated by relations based on power, notions of accumulation through spoliation, and the structural crisis of capital along with the role of the Estate in this process. Amongst our results, we highlight the articulating role played by the Estate towards the accumulation of capital of large mining entities, given that we found a flexible legal arrangement that allowed the appropriation and control of mineral resources by these companies. Mining, in the perspective of the capitalist mode of production, tends to aggregate a territorial expansion that encompasses processes of expropriation, privatization of nature, and social and environmental repercussions that, when combined, might cause in a mild and long term the inhibition of the livelihood of peasants in their territories. These processes generate territorial feuds in the countryside and resistance from local peasants, with the latter as a determinant factor to maintain this social segment as their own historical subjects.